Oriental realities in the creative works of G. Flower-Osnovyanenko (Literatures of the World: Poetics, Mentality and Spirituality, 2013)
The submission of the article explores the artistic creative work in Orientalism G. Kvitka-Osnovyanenko.
Keywords: Orientalism; Oriental realities; romanticism